2006
DOI: 10.1093/ndt/gfl572
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in chronic kidney disease

Abstract: Increasing severity of CKD is associated with progressive cognitive decline and this may have important clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 17 publications
2
72
1
3
Order By: Relevance
“…Vascular dementia may worsen if the patient is treated with dialysis, which may explain why the majority postpone the start of dialysis therapy. [22][23][24] However, respondents stressed that the severity rather than the presence of vascular dementia has a role in their decision making.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofmentioning
confidence: 99%
“…Vascular dementia may worsen if the patient is treated with dialysis, which may explain why the majority postpone the start of dialysis therapy. [22][23][24] However, respondents stressed that the severity rather than the presence of vascular dementia has a role in their decision making.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofmentioning
confidence: 99%
“…30 A number of studies have also found an association between milder forms of chronic kidney disease not requiring dialysis and cognitive impairment. [31][32][33][34][35][36] …”
Section: Association Of Small Vessel Disease In the Brain With Retinamentioning
confidence: 99%
“…CKD is also related to a decrease in quality of life and cognitive function (2). Hypertension and proteinuria promote CKD progression and increase the risk of CVD and mortality (3).…”
Section: Introductionmentioning
confidence: 99%